1993
DOI: 10.1093/bja/70.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Logistic Regression Analysis of Fixed Patient Factors for Postoperative Sickness: A Model for Risk Assessment

Abstract: One hundred and forty-seven patients undergoing minor orthopaedic surgery were studied prospectively by logistic regression analysis to determine the association of independent fixed patient factors with the incidence of postoperative sickness (nausea, retching or vomiting). Gender, history of previous postoperative sickness, postoperative opioids and interaction between gender and previous history of sickness were significant independent factors for postoperative sickness; history of motion sickness was weakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
144
0
17

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(170 citation statements)
references
References 9 publications
9
144
0
17
Order By: Relevance
“…The use of opioid analgesics (e.g. morphine and codeine in this study) is needed to control postoperative pain but they also increase the incidence of PONV 1,34,35 especially in outpatients who become mobile more quickly. 3 6 The use of opioid analgesics did not vary among the study groups (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…The use of opioid analgesics (e.g. morphine and codeine in this study) is needed to control postoperative pain but they also increase the incidence of PONV 1,34,35 especially in outpatients who become mobile more quickly. 3 6 The use of opioid analgesics did not vary among the study groups (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV) is commoner for women, for those prone to motion sickness and when opiates are administered [23,24]. Using our model, described elsewhere [25,26], to study PONV following day case laparoscopy, we compared PONV and other unwanted effects of M6G and morphine.…”
Section: Discussionmentioning
confidence: 99%
“…When administered systemically to animals, the relative potency of M6G to morphine is much closer [3, 5, 8], but in humans the evidence is conflicting, in part because of different methods of assessing analgesia [10][11][12][13][14][15][16][17][18] . M6G has a better toxicity profile for respiratory depression, nausea, sedation, and itching, in humans [11-13, 15, 18-20] if not for animals [9, 21, 22].Postoperative nausea and vomiting (PONV) is commoner for women, for those prone to motion sickness and when opiates are administered [23,24]. Using our model, described elsewhere [25,26], to study PONV following day case laparoscopy, we compared PONV and other unwanted effects of M6G and morphine.…”
mentioning
confidence: 99%
“…Using logistic regression analysis, they concluded that the probability of postoperative sickness in the first 24 hr after surgery can be estimated using the following equation: logit postoperative sickness = -5.03 + 2.24 (postoperative opioids) + 3.97 (previous sickness history) + 2.4 (gender) + 0.78 (history of motion sickness) -3.2 (gender × previous sickness history). 28 Subsequently, Koivuranta studied 1,107 in-patients and used a logistic regression model to generate a score based on the strongest five predictors for PONV: score = 0.93 (if female) + 0.82 (if previous PONV) + 0.75 (if duration of surgery over 60 min) + 0.61 (if nonsmoker) + 0.59 (if history of motion sickness). 16 More recently, in a study of 2,722 patients, Apfel et al developed a simplified risk score consisting of four predictors: female gender, history of motion sickness D Level of evidence based on study design I Large randomized, controlled trial, n $ 100 per group II Systematic review III Small randomized, controlled trial, n < 100 per group IV Non-randomized, controlled trial or case report V Expert opinion Strength of conclusion or recommendation A Good evidence to support the conclusion or recommendation B Fair evidence to support the conclusion or recommendation C Insufficient evidence to recommend for or against or PONV, non-smoking status and the use of opioids for postoperative analgesia.…”
mentioning
confidence: 99%